Transnational media concepts and cases - Mishra, Suman; Kern-Stone, Rebecca (Hoboken, NJ Wiley-Blackwell, 2019)
"Transnational Media: Concepts and Cases provides a clear and engaging overview of media communication from a global and a region-based perspective. Rather than focusing on just complex theories and industry-specific analyses, this unique book offers an inclusive, comparative approach to both journalism and entertainment media--introducing readers to the essential concepts, systems, transnational influences, and power dynamics that shape global media flow. Broad coverage of different media forms from Asia, Africa, the Americas, Europe, and Oceania offers country-based and transnational perspectives while highlighting examples of media trends in television, radio, film, journalism, social media, music, and others. Promoting a balanced, multipolar exploration of transnational media, this innovative book discusses topics such as media concentration, the cultural, political, and economic impact of media, and the primary centers of new and traditional media activities. Chapters organized by geographic region offer instructive pedagogical features--including case studies and essays, and illustrations, maps and charts--that strengthen understanding of distinctive and emerging practices in the production, distribution, and consumption of media products.Explores a wide range of global media topics, infrastructures, cultures, and political-economic climates Written in an engaging, relatable, and easy to understand style Covers major aspects of journalism and various forms of entertainment media Organized by regions of the world to reflect a global perspective Includes newly-written case studies by international scholars from each region Designed for undergraduate and graduate courses in comparative media analysis, international media and communication, and related areas of study"-- Provided by publisher.
Transnational media : key concepts and theories / Suman Mishra -- Introducing media systems / Rebecca Kern-Stone -- Broadcasting in Ghana : opportunities and challenges of a plural media in an evolving African democracy / Isaac Abeku Blankson -- The state of press freedom in South Africa : robust despite the intimidation / Glenda Daniels -- Ushahidi : here comes our testimonies / D. Ndirangu Wachanga -- Nollywood : a cinema of stories / Onookome Okome -- What do they know of telenovela who only telenovela know? : melodrama, passion and Latin America's modern identity / O. Hugo Benavides -- Latin America : from media censorship to media ownership : new forms of communication hegemony across the continent / Fernando Gutierrez and Alejandro Ocampo -- Hollywood, the global media market, and a time of transition for the American media empire / Thom Gencarelli -- The "sanctioned" reggae "revolution," and confrontations between cradles of culture / Humphrey A. Regis -- The social media landscape in China / Xinyuan Wang -- Modern manga / Michael Lewis -- Bollywood : aspirations of a globalizing India / Suman Mishra -- The Korean wave : why it swept the world / Shin Dong Kim -- Al Jazeera and global news : stages of operation / Saba Bebawi -- Public service media in Europe : common values, different political contexts and a variety of practices / Karen Donders -- Sweden and beyond : the pirate party and non-media-centric media politics / Martin Fredriksson -- Bertelsmann SE & Co. KGaA / Scott Fitzgerald -- Broadcasting against the grain : the contradictory roles of RT in a global media age / Liudmila Voronova & Andreas Widholm -- Indigenous media in Australia / Lisa Waller -- The story of Wellywood : how director Peter Jackson conquered the world while remaining in New Zealand / Grant Hannis.
Prof. Shane Carreon (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Mass media; Journalism; International broadcasting